The Implementation of The Concept of Fairness of One Roof- Polygamous Family in The Perspective of Imam Syafi’i - Muhidin, Abd; Jamilah, Jamilah (Islamic Family Law Study Program, Sharia Faculty, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
Polygamy is legal in Islam, but the husband must be able to treat all his wives fairly. Husbands must only be fair in living (food, clothing, and housing) and time division. If all the husband's wives agree, then Islamic law makes it possible to gather all his wives in one place. This article investigates case fairness in three polygamous families living under one roof in Jrengik Sampang. This article aims to discover how polygamy practitioners perceive justice and how it is applied in one-roof polygamous families using the concept of Imam Shafii's fairness. This research is empirical with a qualitative approach. Primary data sources are interviews with informants. secondary data. Sources are books and journals on the justice of polygamy, according to Imam Shafii. This article used data editing, classification, verification, analysis, and field conclusions. Based on the findings of this article, practitioners of polygamous marriages view justice in polygamous families as a necessity and generalize everything outwardly to all wives without exaggerating. The implementation of justice in one-roof Polygamous families in Jrengik District has been going well in their respective ways.